A neurobiological perspective on social influence: Serotonin and social adaptation. Issue 1 (31st March 2022) - Duerler, Patricia; Vollenweider, Franz X.; Preller, Katrin H.
Abstract: Humans are inherently social beings. Being suggestible to each other's expectations enables pro‐social skills that are crucial for social learning and adaptation. Despite their high relevance for psychiatry, the neurobiological mechanisms underlying social adaptation are still not well understood. This review, therefore, provides a conceptual framework covering various distinct mechanisms underlying social adaptation and explores the neuropharmacology — in particular the role of the serotonin (5‐HT) system — in modulating these mechanisms. This article reviews empirical results on social influence processing and reconciles them with recent findings from psychedelic research on social processing to elucidate neurobiological and neuropharmacological underpinnings of social adaptation. Various computational, neurobiological, and neurochemical processes are involved in distinct mechanisms underlying social adaptation such as the multisensory process of social information integration that is crucial for the forming of self‐representation and representations of social norms. This is again associated with self‐ and other‐perception during social interactions as well as value‐based decision‐making that guides our behavior in daily interactions. We highlight the critical role of 5‐HT in these processes and suggest that 5‐HT can facilitate social learning and may represent an important target for treating psychiatric disorders characterized by impairments in social functioning. This framework also has important implications for psychedelic‐assisted therapy as well as for the development of novel treatment approaches and future research directions. Abstract : Our social environment has a constant influence on our behaviour. Nevertheless, our understanding of the neurobiopharmacological underpinnings of social influence processing is still limited. This review provides a conceptual framework covering distinct mechanisms underlying social adaptation. It specifically elucidates the fundamental role of serotonin suggested to facilitate social learning by modulating social information integration. Recent pharmacological challenge studies with psychedelics suggest that in particular the serotonin 2A receptor plays a crucial role in the forming of self‐representations and social norms. Therefore, this framework has important implications for psychedelic‐assisted therapy as well as the development of novel treatment approaches in psychiatry.